Effects of sildenafil on major arterial blood flow using duplex sonography - Kocakoc, E; Ardicoglu, A; Bozgeyik, Z; Kiris, A; Yuzgec, V; Ogur, E (John Wiley & Sons Inc, 2005)
Purpose. Erectile dysfunction (ED) is the persistent inability to achieve or maintain an erection sufficient for satisfactory sexual performance. Oral use of sildenafil citrate is effective in the treatment of ED. Although the effects of sildenafil citrate have been investigated in several systems, its effect on aortic, superior mesenteric (SMA), and carotid artery blood flow is still unclear. The aim of this study is to investigate the early phase effects of sildenafil citrate on aortic, SMA, and carotid artery blood flow using color duplex sonography (CDS). Methods. Thirty-four patients with ED (aged 19-71) were included in this study. Peak systolic velocity, end diastolic velocity, and resistance index (RI) in aorta, SMA, and bilateral common and internal carotid arteries were measured at baseline and 45-75 minutes after the administration of sildenafil citrate using CDS. Results. Statistically significant changes were observed in only 3 of 18 parameters: an increase in post drug values of bilateral internal carotid artery peak systolic velocity (Vmax) compared to baseline values and a significant decrease in the RI value of the left main carotid artery after drug administration compared to baseline values. Conclusions. Sildenafil citrate had no significant effect on aortic and SMA circulation and only caused mild changes in the carotid artery circulation. Although these alterations may be considered clinically insignificant, further studies assessing longterm effects of sildenafil are warranted. (c) 2005 Wiley Periodicals, Inc.
Keywords: sildenafil; Doppler sonography; superior mesenteric artery; side effect; carotid artery; aorta